Enhancement of refrigerant-side condensation heat transfer performance of additively-manufactured air cooled heat exchangers - Lim, Zheng Wei (Nanyang Technological University, 2023)
This report employs both experimental and numerical data as evidence to validate any potential enhancement of the heat transfer performance of a novel air-cooled heat exchanger. For the experimental side, the heat transfer performance of a Selective Laser Melting (SLM) three-dimensional (3-D) printed novel air-cooled heat exchanger with triangular multi-port channels was compared to that of a conventional heat exchanger. R134a refrigerant is first heated to become a high vapour quality mixture and then condensed by passing ambient air in cross-flow within a test section of a wind tunnel. Through numerous experiments, the collected data showed that the novel air-cooled heat exchanger with triangular multi-port channels exhibited a significantly larger heat transfer coefficient than the conventional heat exchanger. This led to additional research to further improve heat transfer performance for the refrigerant side of the heat exchanger, which was investigated through two-dimensional (2-D) simulations. On the numerical front, 2-D simulations were conducted for two-phase condensation of refrigerant R134a under transient conditions using a commercially available software, ANSYS Fluent, where the internal ribbed fin geometries F1, F2, and F3 were investigated. The fins are triangular with varying fin tilt designed to induce vortices in the refrigerant flow, which improves heat transfer performance in the heat exchanger. To better visualise and observe the interface of the vapour-liquid flow, the effects of gravity, interfacial shear stress, and surface tension were factored in by employing the SST k-ω turbulent model and VOF model for the computations. Condensation in simulations was achieved by having ∆T = 10 K between and . Simulation results determined that the channel consisting of F1 fins with a 20 mm pitch exhibited better heat transfer performance compared to geometrically different internal fins F2 and F3. The numerical model was also verified with the results of established numerical and experimental models that compare predicted and experimental ℎ values, with points II lying on the 45° straight line representing the exact agreement between the two values. The numerical model presented in this project portrayed an acceptable degree of accuracy within ± 25%, proving that the simulation results obtained in this project are reasonably reliable.